Implikasi Latihan Yoga Asana Bagi Pembentukan Karakter Siswa Di Ashram Gandhi Puri Sevagram Klungkung - I Wayan Rudiarta (Jayapangus Press, 2020)
Character is a positive values and attitude of life, which is owned by a person so that it influences behavior, way of thinking, acting and ultimately becomes a culture. A person's character will be formed if given positive touches, both physically, mentally and spiritually. One method used is through the practice of yoga asanas as applied at the Ashram Gandhi Puri Sevagram Klungkung. The practice of yoga asanas with the principle of the ashram is able to have implications for changing the character of students towards noble characters. This study focuses on issues concerning the process of forming student’s character through yoga asana exercises and character values ​​formed in students through Yoga asana practice at Ashram Gandhi Puri Sevagram Klungkung. This type of research is qualitative. Data from informants in this research was collected using a purposive technique and to obtain data used several techniques, namely participant observation, in-depth structured interviews, literature studies and documentation studies that were analyzed descriptively qualitatively. The results found that the process of character formation of Ashram students through three stages called kriya yoga, namely Tapah, Svadhyaya, and Isvara Pranidhana. In the Tapah stage, a yoga class is conducted which is correlated with panca kramaning sembah. Character values ​​that are formed from the process of yoga asana practice at Ashram Gandhi Puri are the values ​​of discipline, the value of curiosity, the value of responsibility, the value of hard work, creative value, religious value, and honest values